Antibacterial Compounds Isolated from Endophytic Fungi Reported from 2021 to 2024 - Humberto E. Ortega; Daniel Torres-Mendoza; Luis Cubilla-Rios (Antibiotics, 2025)
Plant endophytic fungi remain a significant source of novel bioactive compounds with uncommon structures rarely found in nature. The discovery of new antibiotics is crucial for combating the growing resistance of pathogenic bacteria, which poses a significant threat to global health. In this review, we examined 132 antibacterial compounds produced by endophytic fungi, reported between January 2021 and December 2024. The most frequently cited fungal genera were Aspergillus and Penicillium, with medicinal plants serving as the primary source of these fungi. Rice was the most used culture medium. A subset of the compounds exhibited biological activity comparable to that of clinically used antibiotics. Some of these molecules may serve as scaffolds for the development of more potent derivatives or synergy studies with antibiotics of medical relevance.